2017
DOI: 10.1590/2358-2936e2017023
|View full text |Cite
|
Sign up to set email alerts
|

Population biology of Macrobrachium jelskii (Miers, 1877) (Decapoda, Palaemonidae) from an artificial pond in Bahia, Brazil

Abstract: The freshwater prawn Macrobrachium jelskii (Miers, 1877) is widely distributed in South America's lentic and lotic habitats. We studied the population structure and reproductive biology of the species in the municipality of Cruz das Almas, state of Bahia, Brazil, to supply information on this ecologically and economically relevant species. Samples were collected monthly, from February 2013 to January 2014, at Laranjeiras pond. The sex ratio was biased towards females (1.4 females : 1 male). The mean carapace l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…According to the current literature, M. iheringi ( Ortmann 1897) (Nogueira et al, ) and some populations of M. amazonicum from water reservoirs (e.g., Pantaleão et al, ; Paschoal, Oliveira, Andrioli, & Zara, ) do not seem to show this characteristic. Some species or populations may lack the differentiation, because differentiation may be driven by the production of peptides by the androgenic glands and regulated by other factors associated with the endocrine physiology of these animals (Paschoal & Zara, ; Rocha & Barbosa, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the current literature, M. iheringi ( Ortmann 1897) (Nogueira et al, ) and some populations of M. amazonicum from water reservoirs (e.g., Pantaleão et al, ; Paschoal, Oliveira, Andrioli, & Zara, ) do not seem to show this characteristic. Some species or populations may lack the differentiation, because differentiation may be driven by the production of peptides by the androgenic glands and regulated by other factors associated with the endocrine physiology of these animals (Paschoal & Zara, ; Rocha & Barbosa, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Williner & Collins (2002), Macrobrachium jelskii males are more active than females. This behavioral difference might be related to the type of reproductive strategy of this species, the pure search (Rocha & Barbosa, 2017). In this strategy, males are highly mobile and their reproductive success depends on their ability to fertilize the highest number of females (Correa & Thiel, 2003;Bauer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Only those having a fully developed appendix masculina were considered adults, since studies indicated that this structure is important during the spermatophore transference and is only functional when fully developed (Bauer, 1976(Bauer, , 2004Berg & Sandifer, 1984). Females were categorized as juveniles or adults based on the average size of sexual maturity (CL = 6.67 mm) estimated by Rocha & Barbosa (2017). Therefore, prawns were separated into five demographic groups: juvenile males, adult males, juvenile females, non-ovigerous adult females and ovigerous adult females.…”
Section: Study Area Specimens Of Macrobrachium Jelskiimentioning
confidence: 99%
“…According to Alekhnovich & Kulesh (2001), the occurrence of reproduction when temperature reaches between 18 and 20°C is apparently a general pattern for Macrobrachium. Reproductive peaks after an increase in pluviosity and temperature were also observed in other species of the genus, M. olfersii (Wiegmann, 1836), M. hainanense (Parisi, 1919) and M. jelskii (Miers, 1877) (Mossolin & Bueno, 2002;Mantel & Dudgeon, 2005;Mossolin et al, 2013;Soares et al, 2015;Rocha & Barbosa, 2017). The recruitment of undifferentiated juveniles occurs in the months after the appearance of ovigerous females, therefore, it is suggested that the reproductive period of M. iheringi is seasonal.…”
Section: Discussionmentioning
confidence: 81%